REGIONAL PROGRAMME OF CITIZENS LABOUR MOBILITY - Nina Mihailovna Pestereva (Science and Innovation Center Publishing House, 2016)
Addressing existing labor shortages in various regions of the country, and especially the Russian Far East (RFE), requires annual public opinion polls to determine the factors that influence the decision on employment of the population outside the place of permanent residence. The main purpose of this study is to assess the ability and willingness of the population of Primorsky krai, the territory of which holds about 31% of the RFE, to move to a new place of residence for permanent or temporary employment. The article presents the results of the pilot sociological survey, jointly organized and conducted by staff of the Far Eastern Federal University and the Department of Labour and Social Development of the Primorsky krai. The results can be used by students, graduate students, research assistants, as well as the regional administration to develop a regional program and monitoring labor mobility, the adjustment of the structure of the state order for training, improvement of retraining programs and training.